2018
DOI: 10.1007/s00431-018-3134-x
|View full text |Cite
|
Sign up to set email alerts
|

Performance and skill retention of five supraglottic airway devices for the pediatric difficult airway in a manikin

Abstract: Supraglottic airway devices (SADs) have been introduced to assist medical professionals in emergency situations with limited experience in securing airways via conventional endotracheal intubation (ETI). Literature on the use of SADs for securing an airway during pediatric critical settings is scarce, and there is a lack of studies comparing different SADs to each other and to conventional ETI. We conducted a study comparing five different SADs to ETI with regard to success rate, time to first ventilation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…This said, in our trial the Singularity TM Air has shown some important disadvantages as compared to the Ambu ® Aura Gain TM . A first-attempt insertion rate of 68% is considerably lower than the 94% for the Ambu ® Aura Gain TM and is certainly unsatisfactory when compared to other studies [25,26]. A possible explanation for this may be found in the soft tip of the Singularity TM Air.…”
Section: Discussionmentioning
confidence: 72%
“…This said, in our trial the Singularity TM Air has shown some important disadvantages as compared to the Ambu ® Aura Gain TM . A first-attempt insertion rate of 68% is considerably lower than the 94% for the Ambu ® Aura Gain TM and is certainly unsatisfactory when compared to other studies [25,26]. A possible explanation for this may be found in the soft tip of the Singularity TM Air.…”
Section: Discussionmentioning
confidence: 72%
“…Still others feature higher device conditioning stiffness and friction coefficients, have a thicker cuff and/or a higher cuff profile, for example, LMA ® -ProSeal™ ,a , 12 LMA ® -Protector™ ,b , 13 Baska-Mask, 14 streamlined liner of the pharynx airway (SLIPA). 15 Therefore, use of some SGDs requires more training, 16,17 and additional adjunct devices may be necessary, such as, for example, an introducer, a stylet, a gum elastic bougie, a gastric tube, [18][19][20] while others can be readily inserted by novices. 21,22 Some SGDs have a preshaped, anatomically curved tube following the normal oropharynx anatomy, or include a fixation tab.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%
“…El videolaringoscopio SMT-II utilizado en una vía difícil permite una mejor visualización de la apertura glótica, un tiempo de operación corto, mejora la tasa de éxito de la intubación. Indica que el videolaringoscopio SMT-II es más seguro que el laringoscopio directo Macintosh en pacientes con vía aérea difícil Ahmadi K et al (2015) 6 Ensayo clínico cuasialeatorizado La GVL (GlideScope video laryngoscope) puede ser una alternativa útil a la laringoscopia directa en situaciones de emergencia y especialmente en casos de vía aérea difícil Kulnig J et al (2018) 7…”
Section: Ensayo Clínico Aleatorizadounclassified